Tuning the response selectivity of graphene oxide fluorescence by organometallic complexation for neurotransmitter detection. Issue 12 (13th March 2019) - Jeon, Su-Ji; Choi, Chanhee; Ju, Jong-Min; Lee, Sin; Park, Jung Hyun; Kim, Jong-Ho
Abstract : Graphene oxide fluorescence is modulated by organometallic complexes for the antibody-free and selective detection of dopamine. Abstract : It is of great interest to design nanomaterial biosensors that can selectively detect target molecules without the use of fragile and expensive antibodies. Here, we report a chemical approach to modulate the response selectivity of graphene oxide (GO) fluorescence for neurotransmitters, in order to design an optical biosensor for the selective detection of dopamine without using antibodies. To this end, GO was functionalized with six different amino acids, followed by the immobilization of seven metal ions, resulting in the production of forty-two different GO nanohybrids (denoted GO-AA-MI derivatives). The fluorescence response of GO-AA-MI derivatives to dopamine, norepinephrine, and epinephrine was modulated by varying the type of amino acids and metal ions introduced. Tyrosine-modified GO with Fe 2+ ions (GO-Y-Fe) exhibited selective quenching of its fluorescence in the presence of dopamine whereas lysine-modified GO with Au 3+ ions (GO-K-Au) showed a selective increase in fluorescence upon addition of norepinephrine. The GO-Y-Fe sensor developed was able to differentiate dopamine from similar structures of norepinephrine and epinephrine, as well as abundant interferents such as ascorbic acid and uric acid, without the use of antibodies. In addition, the GO-Y-Fe sensor successfully detected dopamine secreted from living neuron cells in a rapid and simple manner.